Electronics, communications and networks V : proceedings of the 5th International Conference on Electronics, Communications and Networks (CECNet 2015) /: proceedings of the 5th International Conference on Electronics, Communications and Networks (CECNet 2015). (2016) - Unknown
No abstract available